Evaluation of Milk Yield and Milk Composition of Honamlı Goats - AKBAŞ, AA; TAŞÇI, F; ELMAZ, Ö; SAATCI, M (Journal of the Hellenic Veterinary Medical Society, 2021)
The aim of this study was to determine the milk yield and milk composition (total solids, fat, protein and lactose), freezing point depressionand somatic cell counts of Honamlı goat during second lactationin Turkey. The animal material of the study consisted of a total of 30 goat. Total milk yield was detected by using Fleischmann’s method. Milk composition was analyzed by Bentley 150, and somatic cells were counted by Bentley Somacount FC. One-way ANOVA was used to determine the effect of lactation stages on milk yield and milk composition. In the study, mean lactation period and lactation milk yield of Honamlı goat were detected as 202.4 days, and 92.6 kg, respectively. The percentages of fat, protein, lactose, total solid, freezing point depression, and somatic cell counts /mL of milk were 2.4%, 4.2%, 5.1%, 12.7%, -0.57 °C, 82.8 and 2.9%, 4.2%, 4.7%, 12.7%, -0.59 °C, 483 on the 60th and 120thlactation day respectively. Total solids, fat, and protein values significantly increased especially towards the end of lactation (P <0.05). Lactose value decreased slowly from the beginning to the end of lactation. The somatic cell counts increased in milk particularly at the end of lactation (P < 0.05). The freezing point depression remained stable throughout lactation. It was thought that results of study were important representing the second lactation milk production of Honamlı goats that is one of the native goat breeds of Turkey.